Sperm characters of the digenean Nephrotrema truncatum (Troglotrematidae): a kidney parasite of Crocidura russula (Soricidae) and their phylogenetic significance. Issue 3 (3rd July 2019) - Diagne, Papa Mbagnick; Ndiaye, Papa Ibnou; Bâ, Cheikh Tidiane; Feliu, Carlos; Miquel, Jordi
ABSTRACT: Spermatological characteristics of the troglotrematid digenean Nephrotrema truncatum, a parasite of the shrew Crocidura russula, have been investigated by means of transmission electron microscopy. The ultrastructural study reveals that the mature spermatozoon of N. truncatum exhibits many ultrastructural characters previously described in most gorgoderoideans. These are two axonemes of the 9+'1' trepaxonematan pattern, four attachment zones, a lateral expansion, an external ornamentation of the plasma membrane associated with spine-like bodies and cortical microtubules, and in the posterior part of the anterior spermatozoon region, two bundles of parallel cortical microtubules with the maximum number located in the anterior part of the spermatozoon, a nucleus, two mitochondria, and granules of glycogen. The obtained results are compared with those of other digeneans, particularly the Gorgoderoidea. The sperm cells gorgoderoideans are of type IV, characterised by a 9+'1' pattern of axonemes, the presence of an external ornamentation associated with cortical microtubules and located in the posterior area of the anterior extremity, the presence of two bundles of cortical microtubules, the maximum number of cortical microtubules located in the anterior region of the spermatozoon, and the presence of generally two mitochondria. However, dicrocoeliids and troglotrematids have spermatozoa with ornamentation of the plasma membrane and lateral expansions.